2018
DOI: 10.3389/fmicb.2018.01467
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Acquisition in the First Week of Life

Abstract: Objectives: The fetus is considered sterile but recent studies have suggested that gut colonization could start before birth. Scarce data are available for the acquisition of resistant Gram-negative bacteria (GNB) during the first days of life. Several studies have shown that integrons play a major role in antibiotic resistance acquisition. In this work, we studied the dynamics of human intestinal acquisition of GNB and integrons during the first days of life.Methods: Meconium was collected at birth and a stoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 28 publications
5
14
0
Order By: Relevance
“…{Yu, 2016 #1;Li, 2015 #3} These predominant phyla had also been observed in the fecal samples of humans and animals [34,35]. As mentioned above, a large body of data showed that stabilized microbiota might be disturbed by antibiotics exposure, resulting in chronic and relapsing infections [9][10][11]. The effects of AMX or POL on the human intestinal microbiota have been extensively studied [18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…{Yu, 2016 #1;Li, 2015 #3} These predominant phyla had also been observed in the fecal samples of humans and animals [34,35]. As mentioned above, a large body of data showed that stabilized microbiota might be disturbed by antibiotics exposure, resulting in chronic and relapsing infections [9][10][11]. The effects of AMX or POL on the human intestinal microbiota have been extensively studied [18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 89%
“…As mentioned earlier, exposure to antibiotics may promote the spread of ARB and ARGs in the human gut, which may limit the treatment e ciency and resulting in chronic and relapsing infections [9][10][11]. For instance, ARGs from such classes, including aminoglycosides, beta-lactams, and tetracycline have been con rmed to enrich in human gut microbiota following administration of AMX-clavulanic acid for one week [36], while patients who have taken AMX lower the relative abundance of ARGs from 0.81% to 0.14% [37].…”
Section: Combination Treatment Reduced Occurrence Of Drug Resistance mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the adverse influence of antibiotics on human health has become a public concern since it could cause the dysbiosis of human intestinal microbiota, resulting multiple human diseases [6,7]. Otherwise, antibiotics may also promote the evolution, proliferation, and maintenance of antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the human gut [8,9]. In general, both in vivo and in vitro experiments were widely used in examination of antibiotic influence on gut microbiota [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%